An Ultrahigh Capacity Graphite/Li2S Battery with Holey‐Li2S Nanoarchitectures. Issue 7 (7th May 2018) - Ye, Fangmin; Noh, Hyungjun; Lee, Hongkyung; Kim, Hee‐Tak
Abstract: The pairing of high‐capacity Li2 S cathode (1166 mAh g −1 ) and lithium‐free anode (LFA) provides an unparalleled potential in developing safe and energy‐dense next‐generation secondary batteries. However, the low utilization of the Li2 S cathode and the lack of electrolytes compatible to both electrodes are impeding the development. Here, a novel graphite/Li2 S battery system, which features a self‐assembled, holey‐Li2 S nanoarchitecture and a stable solid electrolyte interface (SEI) on the graphite electrode, is reported. The holey structure on Li2 S is beneficial in decomposing Li2 S at the first charging process due to the enhanced Li ion extraction and transfer from the Li2 S to the electrolyte. In addition, the concentrated dioxolane (DOL)‐rich electrolyte designed lowers the irreversible capacity loss for SEI formation. By using the combined strategies, the graphite/holey‐Li2 S battery delivers an ultrahigh discharge capacity of 810 mAh g −1 at 0.1 C (based on the mass of Li2 S) and of 714 mAh g −1 at 0.2 C. Moreover, it exhibits a reversible capacity of 300 mAh g −1 after a record lifecycle of 600 cycles at 1 C. These results suggest the great potential of the designed LFA/holey‐Li2 S batteries for practical use. Abstract : A highly utilized holey‐Li2 S cathode with an optimized dioxolane‐rich electrolyte constructed graphite/holey‐Li2 S batteries can deliver an ultrahigh discharge specific capacity of 810 mAh g −1 at 0.1 C and 714 mAh g −1 at 0.2 C, and a reversible specific capacity of 300 mAh g −1 with a recording 600 cycles at 1 C.